Childhood atopic dermatitis—Brain‐derived neurotrophic factor correlates with serum eosinophil cationic protein and disease severity. Issue 7 (6th May 2016) - Fölster‐Holst, R.; Papakonstantinou, E.; Rüdrich, U.; Buchner, M.; Pite, H.; Gehring, M.; Kapp, A.; Weidinger, S.; Raap, U.
Abstract: Several studies have shown that neurotrophins including brain‐derived neurotrophic factor (BDNF) play a role in chronic inflammatory skin diseases such as atopic dermatitis (AD). BDNF is increased in the serum samples of adults with AD. Interestingly, eosinophils of these patients can release and produce BDNF. We analyzed BDNF serum levels with ELISA and their correlation with SCORAD score, eosinophil cationic protein (ECP), total IgE, IL‐4, IL‐13 and IL‐31 in children with AD ( n = 56) compared to nonatopic healthy children ( n = 25). In addition, we analyzed FLG loss‐of‐function mutations in 17 children with AD and their connection to BDNF. BDNF serum levels were significantly higher in children with AD. Further, BDNF correlated with disease activity, serum ECP, and total IgE serum levels in AD. There was no difference in BDNF levels of filaggrin‐positive or filaggrin‐negative children with AD, and there was no correlation of BDNF with IL‐31 and Th2 cytokines including IL‐4 and IL‐13. Together, our data add new insights into the pathophysiology of AD, suggesting that serum BDNF which correlates with disease severity contributes to the regulation of inflammation in an eosinophil‐, but not Th2‐dependent manner.